2014
DOI: 10.1007/s11224-014-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on reaction mechanism of an N-heterocyclic carbene boryl azide with electron-deficient alkynes and nitriles

Abstract: A theoretical investigation of the [3?2] cycloaddition reaction of the NHC-boryl azide with alkynes and nitriles has been presented by using the DFT (B3LYP) method. Solvent effects on these reactions have been explored by calculation that included a polarizable continuum model (PCM) for the solvent (C 6 H 6 ). The title reaction could produce two different five-membered products (1,4-regioisomer and 1,5-regioisomer). The reaction pathway involves a one-step mechanism through a [3?2] addition where two nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…PCM is widely used in studies of the solvation effect as the classical quantum chemical calculation method [27]. Many studies show that the results of PCM can be directly compared with the outcome of the experimental measurements,and the results are in good agreement with the experimental values [2830]. To eliminate systematic error between the theoretical and experimental values, the calculations were multiplied by a calibration factor of 0.960 [31].…”
Section: Methodsmentioning
confidence: 99%
“…PCM is widely used in studies of the solvation effect as the classical quantum chemical calculation method [27]. Many studies show that the results of PCM can be directly compared with the outcome of the experimental measurements,and the results are in good agreement with the experimental values [2830]. To eliminate systematic error between the theoretical and experimental values, the calculations were multiplied by a calibration factor of 0.960 [31].…”
Section: Methodsmentioning
confidence: 99%
“…2]-dipolarcycloaddition reactions of 1,3-bis-phenyl-imidazol-2-ylidene dihydridoboron azide with CH 3 C:CCOCH 3 , PhC:CCOOCH 3 , HC:CC 6 H 4 -4-Cl and PhSO 2 C:N, CHCl 2 C:N, F 3 CC:N was studied by Zhang et al [142], who used DFT. The results suggested that two different five-membered products (a 1,4-regioisomer and a 1,5-regioisomer) could be formed.…”
Section: Issuementioning
confidence: 99%